Regulation by Glycogen Synthase Kinase-3 of Inflammation and T Cells in CNS Diseases - Beurel, Eleonore (Frontiers in Molecular Neuroscience, 2011)
Elevated markers of neuroinflammation have been found to be associated with many psychiatric and neurodegenerative diseases, such as mood disorders, Alzheimer's disease, and multiple sclerosis. Since neuroinflammation is thought to contribute to the pathophysiology of these diseases and to impair responses to therapeutic interventions and recovery, it is important to identify mechanisms that regulate neuroinflammation and potential targets for controlling neuroinflammation. Recent findings have demonstrated that glycogen synthase kinase-3 (GSK3) is an important regulator of both the innate and adaptive immune systems' contributions to inflammation. Studies of the innate immune system have shown that inhibitors of GSK3 profoundly alter the repertoire of cytokines that are produced both by peripheral and central cells, reducing proinflammatory cytokines and increasing anti-inflammatory cytokines. Furthermore, inhibitors of GSK3 promote tolerance to inflammatory stimuli, reducing inflammatory cytokine production upon repeated exposure. Studies of the adaptive immune system have shown that GSK3 regulates the production of cytokines by T cells and the differentiation of T cells to subtypes, particularly Th17 cells. Regulation of transcription factors by GSK3 appears to play a prominent role in its regulation of immune responses, including of NF-κB, cyclic AMP response element binding protein (CREB), and signal transducer and activator of transcription-3 (STAT3). In vivo studies have shown that GSK3 inhibitors ameliorate clinical symptoms of both peripheral and central inflammatory diseases, particularly experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis. Therefore, the development and application of GSK3 inhibitors may provide a new therapeutic strategy to reduce neuroinflammation associated with many CNS diseases.